CONFIRMATORY FACTOR ANALYSIS OF CUSTOMER REVISIT INTENTION AT CAFES IN X CITY - Wimaladevi, Putu Kalyana; Setyawati, Christina Yanita (Universitas Ciputra Surabaya, 2018)
Several Cafes in X City are part of food and beverage businesses which is growing rapidly. The Cafes has problems when the turnover that failed to reach the sales target, therefore, it is important to attract new customers and retain old customer. The purpose of this study is to determine the factors that reflect the customer revisit intention at the cafe in X City. This study uses quantitative approach with second-order confirmatory factor analysis method and SmartPLS3 program. A total of 97 customers who visited and made a purchase at cafes located in X City during the research period (April 2017 – November 2018) were chosen as research samples using purposive sampling method. The primary data was collected by distributing questionnaires with Likert scale with 100% rate of questionnaire return. The result of this study shows that food quality, service quality, and store atmosphere reflect customer revisit intention. Additionally, three indicators do not reflect the customer revisit intention: food taste and temperature, waiting time, and music.